Unusual case of isolated frontal sinus mycosis after several years of frontal sinus fracture: case report - Lopez Gonzalez, Demian Manzano; Rubino, Pablo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2014)
Fractures of the frontal sinus account for 5 to 12% of all the maxillofacial fractures. There are different complications related to frontal sinus fractures and some of them may develop even years after the traumatic episode. Isolated fungal infection of the frontal sinus is very exceptional. The most commonly affected paranasal sinus by fungal infection is maxillary sinus. We present an unusual case of isolated fungal infection of the frontal sinus on an immunocompetent patient who had an old frontal sinus fracture that had happened 70 years before. To the best of our knowledge, this is the first reported case in which these particular circumstances coexist.
Keywords: Frontal sinus/injuries; seios paranasais; paranasal sinuses diseases; mycosis